Impact of UV Nanosecond Laser Annealing on Composition and Strain of Undoped Si0.8Ge0.2 Epitaxial Layers. (15th April 2019) - Dagault, L.; Acosta-Alba, P.; Kerdilès, S.; Barnes, J. P.; Hartmann, J. M.; Gergaud, P.; Nguyen, T. T.; Grenier, A.; Papon, A. M.; Bernier, N.; Delaye, V.; Aubin, J.; et al.
Abstract : Ultraviolet Nanosecond Laser Annealing (UV-NLA) was performed on 30 nm-thick Si0.8 Ge0.2 epitaxial layers. The various regimes encountered, depending on the melt depth after single pulse UV-NLA, are described and discussed in this paper. Energy densities around 2.00 J/cm² and above led to the formation of pseudomorphic layers with a strong Ge redistribution. Starting from uniform Si0.8 Ge0.2 layers, Ge segregation toward the surface resulted in the formation of a Ge-rich surface layer with up to 55 at.% Ge for 2.00 J/cm². Such pseudomorphic SiGe layers with a graded composition and a Ge-rich surface may find promising applications such as contact resistance lowering in doped layers.